Young female students in the struggle against Marcos dictatorship in Iloilo City (1972-1986). - Naca, Prida N
The study identifies the factors that led young female students to struggle against the dictatorship in Iloilo City; makes profile of personalities of young female students, identifies and analyzes their forms of resistance; knows the extent in which young female students are motivated by their feminist consciousness to struggle against the dictatorship; and determines their contribution to the continuing struggle for women's liberation., This study employs a liberationist approach and gives light to the woman-focused accounting of history by sharing their own journeys, localizing personalities and situations during Martial Law. The decision of young female students to struggle against the dictatorship could be attributed to the socio-economic and political situation of the country, of the deteriorating state of the Philippine Educational System, of the worsening situation of Filipino women brought about by the country's crisis and the attraction of young intellectuals to Marxism. This was concretized to the condition of Filipino women and of the Filipino people struggle for nationalism and democracy. At the same time, this could be attributed to the development of women's consciousness that enabled them to put into practice theory on how women can be fully liberated. The level of consciousness of young female students determines the form of struggle that they undertook to resist Marcos dictatorial rule. They were evident both in armed and unarmed sphere of the struggle. The study greatly contributes to studies on women especially in contextualizing the historical root of errors committed by the women's movement. This further clarifies the role of the present women's movement to struggle for their class, gender and racial oppression.